PERAN ORANGTUA DALAM PENGAMBILAN KEPUTUSAN ANAK MENJADI TENAGA KERJA WANITA ILEGAL DI DESA LENTO, PROV.NTT - Halima, Yuliana Sulastri; Kebayantini, Ni Luh Nyoman; Nugroho, Wahyu Budi (JURNAL ILMIAH SOSIOLOGI: SOROT, 2019)
ABSTRAC T   This study discusses the role of parents in Lento village in making children’s decisions become illegal female labor abroad, which is seen by George Herbert Mead’s theory of socialization through four social control. The approach of this research using descriptive qualitative method. Technique collection data using observation method, the process of analysis carried out in the form of oral or written words by taking several stages, namely, data reduction, data persentation and drawing conclusions about the role of parents in child decision making into illegal femalelabor in Lento vilagge. The results of research regardig the role of parents in making children’s decisions of children working abroad who are in the background of low family economic pressure and also the desires of the children themselves to work. For children to migrate and work is considered to be away out to improve the family’s economic life.   Keywords: The Role of Parents, Child Decision Making, Illegal Women Labor.